Energy-loss Function for Lead - Nguyen-Truong, Hieu T.; Pham, Tan-Tien; Vu, Nam H.; Ngo, Dang H.; Le, Hung M. (Communications in Physics, 2017)
We study the energy-loss function for lead in the framework of the time-dependent density functional theory, using the full-potential linearized augmented plane-wave plus local orbitals method. The ab initio calculations are performed in the adiabatic local density approximation. The comparison between the obtained energy-loss function for zero momentum transfer with those from reflection electron energy loss spectroscopy measurements and from first-principles calculations shows good agreement.